ICT Adoption and Employee Commitment in Public Sector Institutions: Evidence and Insights from Digital Transformation in Developing Economies - Vincent Kenechukwu Okpala (ASHA Publishing, 2026)
Employee commitment is a critical determinant of public sector performance, particularly in environments undergoing digital transformation. As governments increasingly adopt Information and Communication Technology (ICT) to improve service delivery, administrative efficiency, and governance outcomes, employee attitudes toward technology become central to successful implementation. This paper examines the relationship between ICT adoption and employee commitment in public sector institutions in developing economies. Drawing on the Technology Acceptance Model (TAM), organizational commitment theory, and institutional theory, the paper conceptualizes how digital systems influence employee engagement, affective commitment, and job satisfaction. The study synthesizes existing literature to show that ICT adoption can strengthen employee commitment through improved job efficiency, transparency, and role clarity, while also identifying barriers such as resistance to change, digital literacy gaps, and organizational culture challenges. The paper proposes a conceptual model linking ICT adoption to employee commitment through mediating factors such as perceived usefulness, leadership support, and training. It concludes with policy recommendations for strengthening human-centered digital transformation in public sector organizations.